Optimal placement of nonlinear hysteretic dampers on planar structures under seismic excitation - Martínez, Carlos Alberto (2014)
In the last twenty years great efforts were carried out to develop the concept of energy dissipation in structures to bring it into an applicable technology. Several devices based on different energy dissipation principles have been developed and implemented worldwide. One of the most important tasks for the designer is to deﬁne the locations and sizes of these devices in order to maximize their efﬁciency and safety. In this work, an efﬁciently procedure to optimally deﬁne the energy dissipation capacity of added nonlinear hysteretic dampers, to meet an expected level of performance on planar structures under seismic excitation is proposed. Knowing that the main contribution to the total uncertainty is due to the excitation and with the aim of achieving a robust design, the excitation is modeled as a stationary stochastic process characterized by a power spectral density compatible with a response spectrum deﬁned by seismic code provisions of the region. Since the analysis is performed in the frequency domain, the nonlinear behavior of dampers is included through stochastic equivalent linearization of Bouc'Wen hysteretic model. The proposed procedure is veriﬁed numerically through nonlinear time history analysis using artiﬁcial ground motion records.